∫ − 1 / 3 1 / 3 e x + 1 cos − 1 ( 1 + x 2 2 x ) + tan − 1 ( 1 − x 2 2 x ) d x
If the integral above can be expressed in the form
A B π ,
where A and B are positive integers with B square-free, find A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Let
I = ∫ − 1 / 3 1 / 3 e x + 1 cos − 1 ( 1 + x 2 2 x ) + tan − 1 ( 1 − x 2 2 x ) d x = ∫ − 1 / 3 1 / 3 e x + 1 cos − 1 ( 1 + x 2 2 x ) + sin − 1 ( 1 + x 2 2 x ) d x = ∫ − 1 / 3 1 / 3 2 ( e x + 1 ) π d x = 2 1 . 2 π ∫ − 1 / 3 1 / 3 1 . d x = 4 π . [ x ] − 1 / 3 1 / 3 = 4 3 2 π = 2 3 π A + B = 5 ( tan − 1 ( 1 − x 2 2 x ) = sin − 1 ( 1 + x 2 2 x ) ; ) ( Using the identity sin − 1 a + cos − 1 a = 2 π ; where a ϵ [ − 1 , 1 ] ) ( ∫ − 1 / 3 1 / 3 ( e x + 1 ) 1 d x = 2 1 ∫ − 1 / 3 1 / 3 1 . d x )
Note: tan − 1 ( 1 − x 2 2 x ) = sin − 1 ( 1 + x 2 2 x ) ; because in a right triangle with sides ( 1 + x 2 ) , ( 1 − x 2 ) and 2 x , the given relation holds true.